HOMOMORFISMA PADA SEMIGRUP-Г - Ismania Tanjung Sari; Na'imah Hijriati; Thresye Thresye (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN, 2011)
Abstract algebra is a part of mathematics that studies the principles orrules which will then be used to demonstrate the truth of a statement (theorem).One part of abstract algebra is semigroup and one of it’s generalization is Г-semigroup. An nonempty sets S is called Г-semigroup if  γ, μ  Г and  a, b, c S by aγb  S and (aγb)μc = aγ(bμc). On Г-semigroup, there is theorem ofhomomorphism and called Γ-homomorphism. A mapping  : S T , with S and Tis a Г-semigroup called Γ-homomorphism if  x, y  S dan γ  Г, it’s exist (xγy) =  (x)γ (y).